THE ROLE OF TAX ACCOUNTING IN DETECTING TAX RISKS IN CORPORATE FINANCIAL REPORTS - Eka Septariana Puspa; Windy Permata Suyono; Surya Anugrah (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This research aims to examine the role of tax accounting in detecting tax risks in company financial reports through a literature review approach. In a business environment that is increasingly complex and tightly regulated by tax regulations, tax risk has become a strategic issue that needs to be monitored carefully. Tax accounting not only functions as a tool for recording tax transactions, but also as an analytical instrument capable of identifying potential non-compliance, gaps between commercial and fiscal profits, as well as tax avoidance practices. This research highlights several forms of tax risk such as compliance risk, interpretation risk, and litigation risk, as well as their indicators in financial statements, including significant temporary differences and deferred tax items. The results of the study show that tax accounting plays a key role in building an early detection system for tax risks through reporting transparency and analysis of fiscal information. Thus, tax accounting becomes an integral part of company risk management and contributes to improving the quality of financial reports and compliance with applicable tax regulations.